Sex and teenager in makassar, an education - Asnur Lidayni (JOURNAL OF EDUCATIONAL TECHNOLOGY, CURRICULUM, LEARNING AND COMMUNICATION, 2021)
Society's view of sex education is considered a very personal realm. This departs from a misunderstanding about sex education, as learning about sexual relations. Meanwhile, the phenomenon of sexual violence committed by teenagers in society is increasing. Sexuality education, based on the results of previous research, generally focuses on reproductive health, such as biology and sports. This study aims to provide an overview of the level of understanding of adolescents in Makassar on sex education based on material briefly summarized from PKBI (2015), 1) Form and function of sex organs (2) Reproductive process (3) Healthy and responsible reproduction (4) Actions prevent sexual violence. This study conducted interviews with Twelve Teenagers in Makassar, through the snowball sampling technique. The results showed, in terms of adolescents' understanding of sex education, they included: 1. Sex education vs. sex education, 2. Sex and reproduction education, 3. Sex education vs. sexual violence. and in terms of sources of sex education information, obtained through interviews with Twelve informants. The results of this study indicate that sex education among Makassarese adolescents still needs understanding, and adolescents must have and understand sources of sex education that are valid and in accordance with their psychological development.